O longo caminho dos Corrêa de Miranda no século XIX: um estudo sobre família, poder e economia - ÂNGELO, Helder Bruno Palheta (Universidade Federal do Pará, 2014)
This essay is inserted in the subject of History of the Family and has as an objective to discuss the trajectory of Côrrea de Miranda Family during the XIX Cent., focusing in their economic and political activities and the characteristics of the social relations that were woven through the century. Through the crossing of multiple types of historic sources such as: inventories, wills, journals, provincial presidents reports, chroniclers accounts, among other documents, we will focus to the actions of their members in localities such as Igarapé-Miri, Abaetetuba, Belém e Soure. To begin with, it will be presented the specificities that the Côrrea de Miranda showed by comparison to other traditional families of the XIX cent. paraense scenario.